Hand Foot and Mouth Disease (HFMD) in a 3 Years Old Boy in Bangladesh: A Case Report (Bangladesh Journal of Infectious Diseases, 2020)
Hand, foot & mouth disease (HFMD) is a contagious and emerging infectious disease caused by picorna viridae family. It was first reported in New Zealand in 1957 is caused by Coxsackie virus A16 (CVA16), human enterovirus 71 (HEV71) and occasionally by Coxsackie virus A6 and Coxsackie virus A10, are also associated with HFMD and herpangina. Though only small scale outbreaks have been reported from United States, Europe, Australia Japan and Brazil for the first few decades, since 1997 the disease has noticeably changed its character as noted in different Southeast Asian countries. In recent years Bangladesh also faces some cases of HFMD. Though HFMD is a mild disease but in rare cases may develop neurological complications. Early detection and good clinical assessment can prevent the fatal progression and also can reduce morbidity and mortality regarding HFMD.Bangladesh Journal of Infectious Diseases 2019;6(2):53-55